1949
DOI: 10.1113/jphysiol.1949.sp004347
|View full text |Cite
|
Sign up to set email alerts
|

The changes in water and chloride distribution during heavy sweating

Abstract: Correlated observations on man between changes in salt and water balance and changes in the blood electrolytes during the acute salt loss that occurs during heavy sweating have not been made to the same extent as corresponding observations on animals during acute salt loss otherwise induced. Lee, Murray, Simmonds & Atherton (1941) discussed the strain which working in the heat imposes upon the salt/water balance, but they did not report any figures for the blood electrolyte concentration; their subjects were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1952
1952
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Sweat, secreted to regulate body temperature, becomes a threat to homeostasis of the body fluid, and many reports have been published on changes of body fluids caused by sweating (GLICKMAN et al, 1941;LADELL, 1949;ITOH, 1953;CHRISTENSEN, 1965, 1968;SENAY, , 1970SENAY, , 1972. According to the review by BASS and HENSCHEL (1956), an acute heat stress elicits responses which, in the absence of dehydration, result in increased plasma and blood volumes with little change in their compositions , although the behaviors of extracellular and interstitial fluids are still controversial.…”
mentioning
confidence: 99%
“…Sweat, secreted to regulate body temperature, becomes a threat to homeostasis of the body fluid, and many reports have been published on changes of body fluids caused by sweating (GLICKMAN et al, 1941;LADELL, 1949;ITOH, 1953;CHRISTENSEN, 1965, 1968;SENAY, , 1970SENAY, , 1972. According to the review by BASS and HENSCHEL (1956), an acute heat stress elicits responses which, in the absence of dehydration, result in increased plasma and blood volumes with little change in their compositions , although the behaviors of extracellular and interstitial fluids are still controversial.…”
mentioning
confidence: 99%
“…The chloride still in excess in the body must have been equilibrated by some other mechanisms. As Ladell (17) observed the changes in the chloride concentration of the blood and plasma on a person who heavily sweated, and found that disturbance of the osmotic equilibrium between the extra-and intracellular components which might be expected depending upon the extent to which water and Cl losses are made good, does not develop to any great extent, the equilibrium being quickly restored by simple fluid trasfer.…”
Section: Discussionmentioning
confidence: 99%